The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1155/2012/401613
|View full text |Cite
|
Sign up to set email alerts
|

Medical Robots: Current Systems and Research Directions

Abstract: First used medically in 1985, robots now make an impact in laparoscopy, neurosurgery, orthopedic surgery, emergency response, and various other medical disciplines. This paper provides a review of medical robot history and surveys the capabilities of current medical robot systems, primarily focusing on commercially available systems while covering a few prominent research projects. By examining robotic systems across time and disciplines, trends are discernible that imply future capabilities of medical robots,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
160
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(164 citation statements)
references
References 120 publications
0
160
0
4
Order By: Relevance
“…Many reviews on medical and surgical robotics can be found in the literature. The reader is referred to [42], [43] for reviews on medical robotics, [44] for a tutorial on surgical robotics and [45]- [48] for more recent reviews on surgical robotics.…”
Section: Surgical Robots: Teleoperated Vs Hands-onmentioning
confidence: 99%
“…Many reviews on medical and surgical robotics can be found in the literature. The reader is referred to [42], [43] for reviews on medical robotics, [44] for a tutorial on surgical robotics and [45]- [48] for more recent reviews on surgical robotics.…”
Section: Surgical Robots: Teleoperated Vs Hands-onmentioning
confidence: 99%
“…It is the novel eye tracking and tactile feedback system that distinguish the ALF-X from other surgical robots. [9][10][11][12] This robot has been successfully applied to the clinic. The University of Washington developed RAVEN surgical robot with Phantom Omni haptic devices as master manipulators and four slave manipulators beside the sick bed.…”
Section: Introductionmentioning
confidence: 99%
“…The advanced tendency in that field is oriented to a design of manipulative systems, according to the specifics of concrete orthopedic manipulations [5][6][7]. Some robotized systems are developed aiming to perform specific orthopaedic manipulations automatically [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some robotized systems are developed aiming to perform specific orthopaedic manipulations automatically [7]. Among them, RoboDoc (US), Acrobot (UK), MARS, CRIGOS, CASPAR etc., are well known [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation